A new approach to the calculation of the thermodynamic potential of inhomogeneous electron gas - Kostrobij, P.P.; Markovych, B.M. (Condensed Matter Physics, 2003)
A new approach is proposed to calculate the thermodynamic potential,
which consists in reducing the relevant non-Gaussian functional integral
to its Gaussian form with a renormalized “density-density” correlator. It is
shown that the knowledge of the effective potential of electron-electron
interaction is sufficient to calculate the thermodynamic potential in this
approach. Запропоновано новий підхід для розрахунку термодинамічного потенціалу, який полягає у зведенні відповідного негаусівського функціонального інтегралу до гаусівської форми із перенормованим корелятором “густина-густина”. Показано, що в цьому підході для розрахунку термодинамічного потенціалу достатньо знати ефективний
потенціал міжелектронної взаємодії.